2020
DOI: 10.34172/rdme.2020.016
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesiology residents’ perception towards educational environment using ATEEM in a medical school in Thailand

Abstract: Introduction Educational environment is an important factor in effective teaching and learning. Positive educational environments result in better academic achievements. Administrators are responsible for education at the department and faculty levels, and attention is given to the educational atmosphere by regularly measuring and evaluating various related factors including the subjective level of awareness and perception of residents. A teaching and learning system should include learning and environment ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
1
2
Order By: Relevance
“…Among all the participants, 83 (26.52%) and 17 (5.43%) stated that the operation theater learning environment was moderately desirable and undesirable, respectively. This finding contrasts with a study conducted in Thailand, which reported that only 2.4% and 0% of respondents reported a moderately desirable and undesirable learning environment, respectively [ 31 ]. The difference may be attributed to their use of a different cutoff point for the tool’s category levels.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Among all the participants, 83 (26.52%) and 17 (5.43%) stated that the operation theater learning environment was moderately desirable and undesirable, respectively. This finding contrasts with a study conducted in Thailand, which reported that only 2.4% and 0% of respondents reported a moderately desirable and undesirable learning environment, respectively [ 31 ]. The difference may be attributed to their use of a different cutoff point for the tool’s category levels.…”
Section: Discussioncontrasting
confidence: 87%
“…In this study, 23% and 45.05% of participants perceived operation theater learning environments as very desirable and desirable, respectively. However, these figures are lower than those of similar studies conducted at the University of Witwatersrand (30.6%, 67.1%) and in Thailand (48.4% and 51.6%), respectively [ 3 , 31 ].…”
Section: Discussioncontrasting
confidence: 58%
“…Khan et al 4 in this issue present such an evaluation of the operating theatres in three hospitals affiliated to the University of the Witwatersrand. They took an instrument 5 initially developed and validated in Scotland and subsequently used and validated elsewhere in the world, [6][7][8] and added a question on racial discrimination. Considering the circumstances of operating theatre work, it is perhaps not surprising that an overall score of 67%, while comparable to scores in other countries, leaves 'room for improvement' .…”
Section: Editorialmentioning
confidence: 99%